Impact of COVID-19 outbreak on lifestyle behaviour: A review of studies published in India. Issue 1 (January 2021) - Rawat, Dimple; Dixit, Vivek; Gulati, Sarthak; Gulati, Shreya; Gulati, Arti
Abstract: Background and aims: The entire globe is undergoing an unprecedented challenge of COVID-19 which has affected the lifestyle behaviour of individuals. The present review is an attempt to summarize the effect of pandemic COVID-19 on lifestyle behaviour among the Indian population. Methods: A review was carried out to summarize the effect of pandemic COVID-19 on lifestyle behaviour focusing on changes in dietary or eating behaviour, stress, sleep pattern, and level of physical activity among the Indian population. Literature searches were conducted in PubMed and Google Scholar from inception till October 2020 to identify all relevant studies. Results: A total of 11 studies (n = 5957, age group 18–70 years, comprising both genders) consisting of 1 hospital and 10 community based, were included in the present review. A change in lifestyle behaviour was observed due to COVID-19. Psychosocial or any kind of mental stress among the participants was found to be prevalent. Weight gain and decline in physical activity were also observed. Not only sleep quantity but sleep quality was also found to be affected due to COVID-19. Conclusion: The present review indicates the need for lifestyle behaviour programmes via using the platform of E-media and also for the dissemination of health education. Highlights: Diet, physical activity, sleep, and mental stress levels have been altered during the pandemic (COVID-19). Change in dietary habits than usual was observed in terms of overeating. Reduced physical activity and weight gain were observed. Prevalence of any kind of mental stress particularly levels of anxiety were found to be at highest.